KELIMPAHAN DAN KEANEKARAGAMAN MAKROZOOBENTOS DI SUNGAI BIKNOI, KELURAHAN NAIKOTEN 1, KOTA KUPANG, NTT - Maya Fitriani Roman; Nur Aini Bunyani (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
Macrozoobenthos are aquatic organisms that live at the bottom of the waters with relatively slow movements that are strongly influenced by the basic substrate and the quality of the waters. This study aims to analyze the diversity of macrozoobenthos in the biknoi river, Sub District Naikoten 1, Kupang City. Sampling was carried out at three stations. Station 1 (Bakunase 2 bridge), Station 2 (intlet sluice), and Station 3 (outlet sluice ). Macrozoobenthos samples were taken using purposive random sampling method. Taking macrozoobenthos samples at the bottom of the water using a surber net measuring 25 cm x 40 cm. The results showed that macrozoobenthos found in the Tunan waterfall river consist of 3 phylum, 3 classes, 10 ordo, 20 familia, and 23 genus and 379 individuals. Macrozoobenthic genus that are often encountered are Hydropsyche and the most common macrozoobenthic classis, the Heptageniidae classis. The highest macrozoobenthos diversity index at station 1 (2.69), followed by station 2 (2.31) and the lowest at station 3 (1.94).